Profil Mikroskopis BTA Pada Sputum Keluarga Pasien Terdiagnosa BTA Positif Fase Lanjutan - Imaniah Nur Masitah (Poltekkes Kemenkes Semarang, 2022)
Tuberculosis (TBC) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. The high prevalence of pulmonary tuberculosis in the community, the coverage of the prevention program with the DOTS strategy is still low, so the aspects of controlling transmission risk factors are important, especially transmission of high risk to the families of sufferers. The method of examination performed to diagnose TBC is microscopic examination of sputum. This study aims to determine the microscopic description of Acid Resistant Basil (ARB) in family members who live in one house with patients with TBC smear positive treatment advanced phase at the Balkesmas Semarang area. This research method is descriptive (non-experimental) with total sampling. The results of the study were that there was no ARB in the sputum of family members living in one house with patients with TBC smear positive treatment advanced phase of 31 samples from 17 respondents with 11 (32.3%) sputum samples mixed with saliva, 20 (58.8%) samples saliva and 3 respondents did not give two samples (8.8%). The conclusion of the study is the microscopic description of examination of sputum preparations as many as 31 samples from 17 respondents and 6 families 100% no BTA was found.